Optical Cherenkov Radiation from an Inclined Plate as a Tool for Angular Beam Diagnostics; Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Potylitsyn A. P. Alexander Petrovich; Vukolov A. V. Artem Vladimirovich; Alekseev B. A. Boris Alexandrovich; Atovullaev T. (Cherenkov Radiation, 2019)
Title screen